2017
DOI: 10.3390/urbansci1010006
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Particulate Matter Impact on Human Health within the Urban Environment of Athens City, Greece

Abstract: Abstract:The main objective of this work is the assessment of the annual number of hospital admissions for respiratory diseases (HARD) due to the exposure to inhalable particulate matter (PM 10 ), within the greater Athens area (GAA), Greece. To achieve this aim, on the one hand, time series of the particulate matter with aerodynamic diameter less than 10 µm (PM 10 ) recorded in six monitoring stations located in the GAA, for a 13-year period 2001-2013, have been statistically analyzed. On the other hand, the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 12 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…Public health data and health burden evidence is becoming a key component in policy decisions and action plans, as presented in papers for Greece, Italy, and Iran [16][17][18][19] that can clearly bring considerable health gains for the population. However, contributions to air pollution by sectors needs to be examined, and data made publicly available to steer policy recommendations and decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Public health data and health burden evidence is becoming a key component in policy decisions and action plans, as presented in papers for Greece, Italy, and Iran [16][17][18][19] that can clearly bring considerable health gains for the population. However, contributions to air pollution by sectors needs to be examined, and data made publicly available to steer policy recommendations and decisions.…”
Section: Discussionmentioning
confidence: 99%
“…The AirQ+ model can be used to calculate the total amount of incidents per 100,000 individuals for each concentration level, the associated relative risk, and the total amount of HARD incidents [15]. These findings show that PM2.5 levels are persistently high, pointing to a string of polluted air events that took place in Hillah City in 2022.…”
Section: Relative Risk (Rr)mentioning
confidence: 93%
“…Most of the AirQ studies (187) used ground-monitored air pollution concentrations from the regulatory monitoring network stations alongside modeled and self-measured data, while 8 studies reported they have conducted their own measurements [35,[46][47][48][49][50][51][52]. All but six studies that applied AirQ did not report which type of AQMSs were used [47,[53][54][55][56][57]. For AirQ+, 74% of the studies (65 out of 88) gathered AAP data from the AQMSs, and only 16 studies reported the types of AQMSs used (Supplementary Tables S2, S3) [25,31,36,39,41,[58][59][60][61][62][63][64][65][66][67][68].…”
Section: Exposure Assessmentmentioning
confidence: 99%